Cimitirele medievale de la Buftea–La Cârna/Mănești. O interpretare pe baza monedelor depuse în morminte - Morintz, A.; Coman, M. (Materiale și Cercetări Arheologice)
The present paper aims to provide an interpretation of the dynamics of the largest medieval funerary complex known so far in Wallachia (the site of Buftea – La Cârna/Mănești, generically dated between the 14 th and 17 th centuries), using the coins associated to the burials as a documentary basis. Obviously, such an approach has certain weaknesses, such as the use of a single element of analysis as terminus post quem indicator, the low percentage of burials with coins (less than 7%), etc. However, given the fact that the site was investigated in two distinct stages three decades apart, time bringing great changes in the theory and practice of archaeology, a reference system to report on the various specific aspects of both the earlier and the future research, a system perhaps vulnerable at the moment, but perfectible in time. The purpose of the article is to provide a historical interpretive framework for the archaeological finds from Buftea – La Cârna/Mănești, thus connecting the funerary finds with the socio‑economic and political changes that took place in medieval Wallachia, around Bucharest, from the end of the 14 th to the beginning of the 17 th century.